Bayes estimators of Weibull -Lindley Rayleigh distribution parameters using Lindley's approximation - et. al., Hind Adnan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
For The Weibull Lindley Rayleigh distribution (WLRD) we have obtained the Bayes Estimators of scale and shape parameters using Lindley's approximation (L-approximation) under square error loss function. The proposed estimator have been compared with the corresponding MLE for their risks based on corresponding simulated samples.